The Antecedents for Green Purchasing Initiatives: The Case of Malaysian Technology Based Manufacturing Companies - Jeganathan, Steven Dishan (2012)
In recent years the natural environment becomes a major global issue. Due to increasing human and industrial impacts on the environment, environmental issues become more intense and widespread. In this regard, businesses need to place equal footing both on the environment and on their business objectives. This paper is an attempt to clarify the path towards that end and examine the factors for Green Purchasing Initiatives and show the steps that have to be taken by business organizations through green supply chain to make sustainable development a reality. This research is established based on two theoretical lenses – Green Purchasing and Critical Success Factors (CSF). Specifically the paper is interested to investigate the factors namely Regulation (RG), Social Responsibility (SR), and Expected Business Benefits (EBB) on Green Purchasing Initiatives (GPI) in the Malaysian technology based manufacturing sector that leads to Green Supply Chain Initiatives. The ISO 14001 Environmental Management System standard has become a widespread administrative tool towards corporate environmental management. It was introduced in 1996, and has been adopted by over 60, 000 firms around the world, including Malaysia. Hence the survey data was obtained from ISO 14001 certified technology based manufacturing firms in Malaysia which was obtained from the Federation of Malaysian Manufacturers Directory 2011 43rd edition. The survey was conducted using structured postal questionnaire directed to the Environmental Management Representative (EMR) in each firm. The empirical findings of the study suggest that Green Purchasing Initiative is affected by the drivers namely Regulation and Expected Business Benefits. The results also suggest that, although Malaysian firms show a high level of Social Responsibility, it does not constitute a genuine driver for these firms to adopt Green Purchasing Initiatives.